2013
DOI: 10.2298/pif1304239p
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits and population growth of greenhouse whitefly (Trialeurodes vaporariorum westwood) on different tomato genotypes

Abstract: SuMMARYThe effects of five tomato genotypes (cv. Narvik and hybrids NS-6, Tamaris, Alliance and Marko) on the survival, reproduction, development and population growth of the greenhouse whitefly Trialeurodes vaporariorum were examined. A laboratory population of T. vaporariorum had been reared on tobacco plants for three years before the study. Females that laid eggs on the genotype Marko lived significantly longer and their offspring needed significantly shorter periods to develop than females on the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Whiteflies are important agricultural pests with a global distribution (Anderson et al, 2004; Lapidot et al, 2014). Their agricultural importance is associated with damage caused during feeding on the plant phloem and in the production of honeydew (Colvin et al, 2006; Prijović et al, 2013). Honeydew serves both to reduce transpiration and as an inoculation point for saprophytic fungi, which grow over the leaf surface reducing photosynthesis (Colvin et al, 2006).…”
mentioning
confidence: 99%
“…Whiteflies are important agricultural pests with a global distribution (Anderson et al, 2004; Lapidot et al, 2014). Their agricultural importance is associated with damage caused during feeding on the plant phloem and in the production of honeydew (Colvin et al, 2006; Prijović et al, 2013). Honeydew serves both to reduce transpiration and as an inoculation point for saprophytic fungi, which grow over the leaf surface reducing photosynthesis (Colvin et al, 2006).…”
mentioning
confidence: 99%
“…Kapantaidaki et al (2014) supported these findings using a combination of mtCOI and secondary endosymbionts. In addition, Prijović et al (2013) reported a similar lack of phylogeographical structuring across populations in Serbia and surrounding countries. However, some studies have reported population structuring in different regions, with several drivers implicated as influencing population structure.…”
Section: Phylogeographical Structure Of T Vaporariorum In Sub-saharamentioning
confidence: 83%
“…Whiteflies are important agricultural pests with a global distribution (Anderson et al, 2004; Lapidot et al, 2014). Their agricultural importance is associated with damage caused during feeding on the plant phloem and the production of honeydew (Colvin et al, 2006; Prijović et al, 2013). Honeydew serves both to reduce transpiration and as an inoculation point for saprophytic fungi which grows over the leaf surface reducing photosynthesis (Colvin et al,2006).…”
mentioning
confidence: 99%
“…They considered to be one of the most significant plant pests and colonizes over 600 host plants, causing significant damage (Polston et al 2014). This specie of whitefly is distributed globally (De Barro 1995; De Barro et al 2000; De Barro et al 2005) and causes significant damage to crop yield and quality by feeding on plant phloem and secreting honeydew that stimulates the rapid growth of molds (Colvin et al 2006;Prijović et al 2013). However, the most significant problem associated with outbreaks of B. tabaci is the transmission of plant viruses (Navas-Castillo et al 2011).…”
Section: Introductionmentioning
confidence: 99%